Green fabrication of unoxidized graphene by combination of frozen dispersion and multimode microwave thermal shock - Yusuke Ebato; Yamato Hayashi; Hirotsugu Takizawa (Cleaner Engineering and Technology, 2023)
Next-generation electronic materials must be produced and used sustainably. Nanocarbon materials have attracted much attention as next-generation materials because they have excellent properties and can be made from readily available and inexpensive raw materials. Among them, graphene is highly expected as a material that realizes high performance and energy saving in electric devices. It has excellent properties such as high electrical conductivity, high strength, and light weight. However, the current synthesis method for graphene requires the use of toxic chemicals such as strong oxidants and a large amount of energy consumption due to use of high vacuum and high temperature. Those requirements increases the environmental impact and cost. Therefore, a simple, environmentally friendly, inexpensive, and innovative process is required for the practical use of graphene. We have developed a novel process with a new mechanism using inexpensive and safe raw materials such as graphite, ice, and simple organic solvents and general equipment such as a microwave oven. The combination of the thermal expansion properties of graphite and the selective heating properties of microwaves created the new process. This paper shows that graphene synthesis can be achieved easily and cost-effectively using familiar equipment and materials by combining fundamental physical properties and phenomena.